Cultures of Sound Network: The Genesis of an International Alliance - Ostashewski, Marcia; Berger, Harris M.; Bernard Sr., Darrell; Clark, Logan E.; Frishkopf, Michael; Klassen, Judith; Loughran, Maureen; Marshall, Graham (MUSICultures, 2025)
The Cultures of Sound Network is an international alliance of cultural institutions that develops public engagement projects around music and sound. Since its inception in 2018, the network has used collaborative inquiry to mobilize music and sound knowledge across North America and beyond, serve diverse communities, including Indigenous ones, and bridge divides between museums, universities, cultural organizations, and publics. This article discusses examples of the network’s modus operandi and examines the value, significance, and prospects for sound initiatives of this kind in the 2020s.